ผลของโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคมต่อพฤติกรรมการออกกำลังกายของหญิงมีครรภ์ Effect of a Self-efficacy Enhancement and Social Support Program on Exercise Behavior Among Pregnant Women - ปานเกษม, สุวิสา (Journal of The Royal Thai Army Nurses, 2013)
บทคัดย่อ การออกกำลังกายในระหว่างตั้งครรภ์ก่อให้เกิดประโยชน์ทั้งต่อมารดาและทารกในครรภ์ การวิจัยแบบกึ่งทดลองครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาผลของโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคมต่อพฤติกรรมการออกกำลังกายของหญิงมีครรภ์ กลุ่มตัวอย่างเป็นหญิงมีครรภ์ที่มารับบริการฝากครรภ์ที่หน่วยฝากครรภ์โรงพยาบาลพระมงกุฎเกล้า จำนวน 30 ราย ระหว่างเดือนพฤษภาคม พ.ศ. 2554 ถึงเดือนมิถุนายน พ.ศ. 2555 คัดเลือกกลุ่มตัวอย่างตามคุณสมบัติที่กำหนด แบ่งเป็นกลุ่มควบคุมและกลุ่มทดลองเท่า ๆ กัน กลุ่มละ 15 คน โดยกลุ่มควบคุมได้รับการดูแลตามปกติ ส่วนกลุ่มทดลองได้รับโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคม เครื่องมือที่ใช้ในการวิจัยครั้งนี้ ประกอบด้วย โปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคมในการออกกำลังกาย และ แบบสอบถามพฤติกรรมการออกกำลังกายของหญิงมีครรภ์ วิเคราะห์ข้อมูลโดยใช้สถิติพรรณนา และสถิติทดสอบที ผลการวิจัยพบว่า คะแนนเฉลี่ยพฤติกรรมการออกกำลังกายของหญิงมีครรภ์กลุ่มทดลองภายหลังเข้าร่วมโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคม สูงกว่ากลุ่มควบคุม อย่างมีนัยสำคัญทางสถิติ (p<.001) คะแนนเฉลี่ยพฤติกรรมการออกกำลังกายของหญิงมีครรภ์กลุ่มทดลองภายหลังเข้าร่วมโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคมสูงกว่าก่อนเข้าร่วมโปรแกรม อย่างมีนัยสำคัญทางสถิติ (p<.001) ผลการศึกษาแสดงว่าโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนทางสังคม สามารถส่งเสริมให้หญิงมีครรภ์มีพฤติกรรมการออกกำลังกายเพิ่มขึ้นในระหว่างตั้งครรภ์ คำสำคัญ : การส่งเสริมสมรรถนะแห่งตน การสนับสนุนทางสังคม การออกกำลังกาย หญิงมีครรภ์ ABSTRACT Exercise during pregnancy has benefits for both the mother and the fetus. This quasi-experimental research aimed to examine the effect of the self-efficacy promotion and social support program on exercise behavior among pregnant women. The subjects consisted of 30 pregnant women who attended the antenatal clinic at the Royal Thai Army Hospital from May 2011 to June 2012. They were selected according to the inclusion criteria and assigned in equal numbers to the control and experimental groups, fifteen women in each group. The control group received routine antenatal care whereas the experimental group received the designed program. The research instruments used in this study were the self-efficacy promotion and social support program and the exercise behavior of pregnant women questionnaire. Data were analyzed using descriptive statistics, independent t-test and paired t-test. The findings of this study revealed that: 1. The exercise behavior mean score of the pregnant women in the experimental group after participating in the self-efficacy promotion and social support program was statistically significantly higher than that of the control group (p < .001). 2. The exercise behavior mean score of the pregnant women in the experimental group after participating in the self-efficacy promotion and social support program was statistically significantly higher than their score before participating in the program (p < .001). The results of this study indicate that the self-efficacy promotion and social support program promote pregnant women to increased exercise behavior during pregnancy. Keyword : Self-efficacy Promotion, Social Support, Exercise, Pregnant Women